2006
DOI: 10.1021/ja057973p
|View full text |Cite
|
Sign up to set email alerts
|

Ladder Polyether Synthesis via Epoxide-Opening Cascades Using a Disappearing Directing Group

Abstract: The combination of a trimethylsilyl group, a Brønsted base, a fluoride source, and a hydroxylic solvent enables the first construction of the tetrad of tetrahydropyran rings found in the majority of the ladder polyether natural products by way of a cascade of epoxide-opening events that emulates the final step of Nakanishi's proposed biosynthetic pathway. The trimethylsilyl group disappears during the course of the cascade, and thus these are the first epoxide ring-opening cascades that afford ladder polyether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 19 publications
(9 reference statements)
2
42
0
3
Order By: Relevance
“…An illustrative example is found with the titanium-promoted cyclization of the highly oxygenated bicyclic epoxide 537 to give the spiroketal 538 with retention of configuration [593]. Similar intramolecular processes have been catalyzed by caesium [594] and p-toluenesulfonic acid [595]. In one such intramolecular epoxide ring opening -a key step in the diastereoselective synthesis of a-tocopherol -anhydrous hydrochloric acid in ether/acetonitrile was chosen to promote the disfavored 6-endo-tet ring closure mode [596].…”
Section: Oxiranes J93mentioning
confidence: 99%
“…An illustrative example is found with the titanium-promoted cyclization of the highly oxygenated bicyclic epoxide 537 to give the spiroketal 538 with retention of configuration [593]. Similar intramolecular processes have been catalyzed by caesium [594] and p-toluenesulfonic acid [595]. In one such intramolecular epoxide ring opening -a key step in the diastereoselective synthesis of a-tocopherol -anhydrous hydrochloric acid in ether/acetonitrile was chosen to promote the disfavored 6-endo-tet ring closure mode [596].…”
Section: Oxiranes J93mentioning
confidence: 99%
“…However, when a cascade reaction under the same Lewis acid conditions was attempted on diepoxide 256, with suitably positioned silyl groups, the only isolable product was bis-tetrahydrofuran 257 (Scheme 15.20a) [198]. Thorough evaluation of reaction conditions revealed that the outcome of this reaction was very different when a Brønsted base in alcoholic solvents was used.…”
Section: Epoxide-opening Cascades In the Synthesis Of Polycyclicmentioning
confidence: 99%
“…Surprisingly, the trimethylsilyl directing group was absent from the ring junction in the product. Further modification to the design of polyepoxide substrates and reaction conditions resulted in the development of epoxide-opening cascades directed by ''disappearing'' silyl groups (Scheme 15.20b) [198]. These modifications included the pre-formation of one THP ring in substrates 259, 262, and 265 prior to the cascade and the addition of CsF to the reaction mixture.…”
Section: Epoxide-opening Cascades In the Synthesis Of Polycyclicmentioning
confidence: 99%
“…310 Interestingly, when this Lewis acid is used with the diepoxyde 157, the 5-exo-ditetrahydrofuran 158 is obtained in a ladder polyether fashion, whereas the more interesting natural product-containing tetrahydropyrane dyad 159 is generated after treatment of compound 157 with cesium carbonate (Scheme 49). 311 The boron-trifluoride epoxide oxacyclization has also applied to triepoxides, leading to bisoxepanes. …”
Section: Scheme 48mentioning
confidence: 99%